Analysis of Indonesian and Thai Governments Policies in Handling Human Trafficking Cases (2021-2023) - Al-Hammad, Ahmad Idris (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study contrasts the policies of the Indonesian and Thai governments in handling human trafficking cases (2021-2023). Human trafficking is the crime of commercially trading human beings either through sexual exploitation or forced labour. As ASEAN countries, Indonesia and Thailand contribute to the number of these crimes. Throughout 2021-2023, the human trafficking tier-placement in both countries showed fluctuating conditions but also continued to increase. The role of the government is needed in efforts to handle this case, although its implementation also involves massive collaboration from various components. A descriptive qualitative methodology centred on library research analysis was selected as the primary way for acrticulating the findings of this study. By comparing secondary data consisting of various literatures and applying the Advocacy Coalition Framework (ACF) theory, the findings in this study show that the policies of the Indonesian and Thai governments in handling human trafficking cases have not been fully maximized. Nevertheless, the presence of interest groups is very influential in supporting the process of monitoring, formulating, and evaluating more optimal government policies.